Perbedaan Pengetahuan dan Sikap Remaja Tentang Keamanan Makanan Jajanan Antara Sebelum dan Sesudah Pendidikan Media Cergam Di SMP Negeri 1 Kebakkramat Karanganyar - Susanti, Oktavia Candra; , Eni Purwani, S.Si., M.Si; , Susi Dyah Puspowati, SP., M.Si (2015)
Background: Students' street-food safety awareness in Indonesia still low, either of the microbiology quantity or the harmful chemical substances. Earlier survey on knowledge of State Junior High School 1 of Kebakkramat especially about the street-food safety, out of 20 sampelts, all of them had low knowledge. Objective: This research intended to understand the differences in knowledge and attitudes of street-food safety of adolescents before and after education using picture book at State Junior High School 1 of Kebakkramat Karanganyar. Research Method: This was a quantitative research using quasi experimental with one group pre-post test design. The Number of sampelts was 71 student. Knowledge variable was tested using Wilcoxon Sign Test, while attitude variable was tested using Paired T-Test. Result: Before the nutrition education was given only 36,6% of students had good knowledge and 63,4% had poor knowledge. Meanwhile, after receiving the nutrition education, all students had good knowledge. Attitudes of students' who were supporting street-food safety increased from only 18,3% to 91,5%. Meanwhile, attitudes of students' who were not supporting street-food safety decreased from only 81,7% to 8,5%. Conclusion: There were differences in knowledge and attitudes of students on street-food safety before and after education using picture book (p value=0,000).